Deep brain stimulation for Parkinson’s disease in Pakistan: current status, opportunities and challenges - Nabeel Muzaffar Syed; John Bertoni; Danish Ejaz Bhatti (Journal of the Pakistan Medical Association, 2020)
Abstract Parkinson’s disease is a slowly progressive neurodegenerative disease that commonly affects people aged 60 years and above. So far, no treatment has been shown to halt or slow the progression of the disease and our options are limited to symptomatic management. Levodopa is the most preferred antiparkinsonian medication that provides excellent control of symptoms early in the disease. However, in most patients the response declines over time and complications of motor fluctuations and dyskinesia arise. Other medical therapies play an adjunctive role in the management, as they are not as effective as levodopa. Advanced therapies like deep brain stimulation (DBS) can provide effective control of symptoms in moderate to advanced disease. Deep brain stimulation surgery has recently been started in Pakistan. This review provides an overview of deep brain stimulation, its indications, patient selection process and details of surgery, Continuous......